Peculiarities of Data Interpretation upon Direct Tissue Analysis by Fourier Transform Ion Cyclotron Resonance Mass Spectrometry. Issue 3 (June 2016) - Chagovets, Vitaliy; Kononikhin, Aleksey; Starodubtseva, Nataliia; Kostyukevich, Yury; Popov, Igor; Frankevich, Vladimir; Nikolaev, Eugene
The importance of high-resolution mass spectrometry for the correct data interpretation of a direct tissue analysis is demonstrated with an example of its clinical application for an endometriosis study. Multivariate analysis of the data discovers lipid species differentially expressed in different tissues under investigation. High-resolution mass spectrometry allows unambiguous separation of peaks with close masses that correspond to proton and sodium adducts of phosphatidylcholines and to phosphatidylcholines differing in double bond number.